2012
DOI: 10.1007/s00520-012-1464-1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the informational and psychosocial needs of Chinese immigrant cancer patients: a focus group study

Abstract: Purpose The Chinese immigrant community faces multiple barriers to quality cancer care and cancer survivorship. Psychosocial interventions can positively impact quality of life, anxiety, and distress in cancer patients. In this study, we explored the informational and psychosocial needs of Chinese cancer patients to inform development of culturally targeted support and survivorship interventions. Methods We conducted four focus groups with a total of 28 Chinese cancer patients to elucidate their cancer infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 37 publications
3
55
0
Order By: Relevance
“…However, one could argue that receiving adequate information is even more important for this population underrepresented by our study, as language barriers have been demonstrated to make patients vulnerable to misunderstanding and confusion. [31][32][33] Another potential selection bias is that survey respondents may be more likely than nonrespondents to have been dissatisfied with the information they received, as they would have more of a reason to express their opinion through taking the survey. Nevertheless, it is noteworthy that 93% of individuals who responded wanted at least half of the survey questions answered.…”
Section: Discussionmentioning
confidence: 99%
“…However, one could argue that receiving adequate information is even more important for this population underrepresented by our study, as language barriers have been demonstrated to make patients vulnerable to misunderstanding and confusion. [31][32][33] Another potential selection bias is that survey respondents may be more likely than nonrespondents to have been dissatisfied with the information they received, as they would have more of a reason to express their opinion through taking the survey. Nevertheless, it is noteworthy that 93% of individuals who responded wanted at least half of the survey questions answered.…”
Section: Discussionmentioning
confidence: 99%
“…Also, both patients and doctors felt more satisfied when the doctor checked the patient's understanding. [58,72,[84][85][86][87][88][89] For example, paraphrasing and repeating the patient's exact words encouraged the patient to elaborate on their concerns. [90] Together, the communication objectives, the core skills and the specific skills would help to facilitate successful communication between doctors and patients.…”
Section: Language Differencesmentioning
confidence: 99%
“…Finally, patients were queried on whether they were ever advised not to use TCM by a Western doctor, and if they would be interested in learning more about TCM and potential interactions with cancer treatment, as well as potential toxicities due to TCM. Questions were developed based on prior qualitative work exploring the needs of Chinese immigrant cancer patients [23]. …”
Section: Design and Participantsmentioning
confidence: 99%